Kala (Time): The Crucial Element in Understanding Health and Disease in Ayurveda - Parvathy Prakas Seethalekshmy; Leena Parameswaran Nair; Meera Esanamangalam; Haritha Chandran (AYUSHDHARA, 2025)
Time or Kala is the principal reason for the continuous cycle of birth and death among organisms and Ayurveda has given great importance to Kala for the healthy as well as the diseased. Kala is one among the Navakarana dravyas and is also known as Parinama, as everything in this universe undergoes change with time in a definite order. Ayurveda considers Kala as Kshanadi and Vyadhyavastha. Susruthacharya takes time as Dina Ritu Kala, where Dina is Poorva and Aparahna and Ritukala as Adana and Visarga kala comprising of Shadrtus. The Shadkriyakalas explained in the classics also implies the importance of giving medications in time so as to prevent the pathogenesis of diseases. Similarly, Kala plays an important role in Vyadhyavastha, for obtaining the prognosis of a disease. The Oushadhasevanakalas mentioned in Brihattrayees are very important for the successful treatment of Vyadhis. The Heena, Mithya and Athiyogas of Kala, Artha and Karma are the prime causative factor for diseases. Even in ascertaining the Prakriti of an individual, time has a very crucial role. Thus, Kala is invariably connected to an individual – whether in preventive or curative aspects.